Variation in Wood Specific Gravity of Pinus radiata in Victoria, Australia - Shirin, Fatima; Kumar, Dinesh; Pederick, Leon (Indian Forester, 1998)
The results of analysis of variance for specific gravity and ring width between three clones of Pinus radiata selected in eleven individual trees of thirty years of age in a plantation are reported.